2018
DOI: 10.1111/1468-5973.12250
|View full text |Cite
|
Sign up to set email alerts
|

The face tells all: Testing the impact of physical attractiveness and social media information of spokesperson on message effectiveness during a crisis

Abstract: This paper empirically examines the effects of organizational spokesperson's physical attractiveness and their social cues usage on message effectiveness. A 2 (physical attractiveness of spokesperson) × 2 (social cues) × 2 (crisis response strategy) mixed subject design was tested. The results show that spokespeople with high physical attractiveness as communicating more credible messages, being more expert sources, and as being more persuasive. Also, social cues of spokespeople have an influence on the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(56 reference statements)
2
5
0
1
Order By: Relevance
“…The personal branding theory suggests that an attractive personal image can influence viewer judgment (Goffman, 1959), implying that doctors with good looks may attract more viewer attention and responses. Previous research supports this idea, indicating that individuals with better appearance tend to be more persuasive and influential due to their perceived reliability and professionalism (Hong et al, 2019;Koernig and Page, 2002;McCroskey, 1982). Furthermore, camera shooting angles can also shape the doctor's image, with straight-shooting angles indicating greater engagement, immersion, social presence and entertainment for viewers (Wang, 2020).…”
Section: Health Science Short Video Viewer Engagementmentioning
confidence: 87%
See 2 more Smart Citations
“…The personal branding theory suggests that an attractive personal image can influence viewer judgment (Goffman, 1959), implying that doctors with good looks may attract more viewer attention and responses. Previous research supports this idea, indicating that individuals with better appearance tend to be more persuasive and influential due to their perceived reliability and professionalism (Hong et al, 2019;Koernig and Page, 2002;McCroskey, 1982). Furthermore, camera shooting angles can also shape the doctor's image, with straight-shooting angles indicating greater engagement, immersion, social presence and entertainment for viewers (Wang, 2020).…”
Section: Health Science Short Video Viewer Engagementmentioning
confidence: 87%
“…Social psychology research has suggested that there is a rule of thumb that states "what is beautiful is good," which means that people with better looks are perceived to have exceptional interpersonal characteristics and are more likely to form social relationships (Dion et al, 1972). Better-looking individuals tend to be more persuasive and more possible to change other's opinion due to the fact that the information they convey is considered more reliable and professional (Hong et al, 2019;Koernig and Page, 2002;McCroskey, 1982). This idea can explain why doctors with a better appearance are seen as more reliable and professional, which in turn, makes viewers more likely to engage with their videos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menurut Kupta, personal branding adalah sebuah pencitraan pribadi yang mewakili serangkaian keahlian, suatu ide cemerlang, sebuah sistem kepercayaan, dan persamaan nilai yang dianggap menarik oleh orang lain (Sthephens, 2007) lebih efektif (Wojciechowska, 2021). Seseorang yang memiliki style atau daya tarik akan lebih mudah untuk mempersuasi orang lain (Hong et al, 2019)…”
Section: Pendahuluanunclassified
“…In fact, a great deal of existing research has focused on how the source or spokesperson presenting a message can influence audience perceptions (e.g., [ 40 – 42 ]). Such research has examined variables including a spokesperson or source’s role or title [ 41 ], attractiveness [ 43 ], and gender [ 44 ]. Related scholarship has explored source effects based on narrative perspective or how a source is related to the information at hand, meaning whether the narrative is told in the first- or third-person.…”
Section: Introductionmentioning
confidence: 99%